Measuring Artificial Recharge with Fiber Optic Distributed Temperature Sensing. Issue 5 (30th October 2012) - Becker, Matthew W.; Bauer, Brian; Hutchinson, Adam
<x xml:space="preserve">Abstract</x> Heat was used as a tracer to measure infiltration rates from a recharge basin. The propagation of diurnal oscillation of surface water temperature into the basin bed was monitored along a transect using Fiber Optic Distributed Temperature Sensing (FODTS). The propagation rate was related to downward specific discharge using standard theory of heat advection and dispersion in saturated porous media. An estimate of the temporal variation of heat propagation was achieved using a wavelet transform to find the phase lag between the surface temperature diurnal oscillation and the correlated oscillation at 0.33 and 0.98 m below the bed surface. The wavelet results compared well to a constant velocity model of thermal advection and dispersion during periods of relatively constant discharge rates. The apparent dispersion of heat was found to be due primarily to hydrodynamic mechanisms rather than thermal diffusion. Specific discharge estimates using the FODTS technique also compared well to water balance estimates over a four month period, although there were occasional deviations that have yet to be adequately explained. The FODTS technique is superior to water balance in that it produces estimates of infiltration rate every meter along the cable transect, every half hour. These high resolution measurements highlighted areas of low infiltration and demonstrated the degradation of basin efficiency due to source waters of high suspended solids. FODTS monitoring promises to be a useful tool for diagnosing basin performance in an era of increasing groundwater demand.